Innovative Approaches to Creating Training Phraseological Dictionary as Interactive Hypertext - Nikitina, Tatiana; Rogaleva, Elena (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The article reviews material on Russian training phraseography, in particular, it contains an analysis of the disadvantages of the interpretation of idioms in phraseological dictionaries for primary school learners. The author presents her own technology of creating an innovative phraseological dictionary for primary school children which combines traditional principles for describing idioms in phraseological dictionaries with stimulation of an interactive dialogue between the author and the young reader. As a result, the interactive hypertext of a non-computer dictionary approximates to an electronic dictionary and an educational computer game that satisfies primary school learners’ demand and facilitates children’s learning idioms.